Effects of Divorce in the Happiness of Children - Maksutaj, Fabjana Bakiu (European Scientific Journal, ESJ, 2021)
This study investigates the impact that parent’s divorce has on the happiness of Albanian children in the city of Tirana. The age group was determined to be from 13 to 18 years old, because it related to adolescence, which is a difficult stage in which the child is prepared for the transition as an adult. The goal is to measure the level of happiness according to the subjective perception of the children for the time when they lived with both parents, and after that of divorce. Its achievement was accomplished by setting of such goals as: was the child happy before the divorce of the parents, is he happy after it now? Is he happy with the life he leads and would he liked to live with both parents again? If yes, what would it change in his life and would his happiness increase? Methodology involves a primary survey with the help of a structured questionnaire among 405 children from 19 public elementary and high schools in Tirana. The consequences of divorce to happiness of children are theoretically explained and give the opportunity to raise research questions in recent years. The research instrument includes questions about the level of happiness before and after parental divorce and the impact of parents‘ relationships after divorce on happiness for this segment of children. The data analyse have led to conclusions and recommendations on social policies to be followed towards this segment in the future.